2014
DOI: 10.1088/1367-2630/16/12/123037
|View full text |Cite
|
Sign up to set email alerts
|

X-ray measurements in helium-like atoms increased discrepancy between experiment and theoretical QED

Abstract: p ) found a major discrepancy with quantum electrodynamics (QED) and independent nuclear size determinations. Here we find a significant discrepancy in a different type of exotic atom: a medium-Z nucleus with two electrons. Investigation of the data collected is able to discriminate between available QED formulations and reveals a pattern of discrepancy of almost six standard errors of experimental results from the most recent theoretical predictions, with a functional dependence proportional to Z n where ≃ n … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…When older calculations were used as a reference, we used the energies of Ref. [59] to obtain an updated value for this table. A detailed analysis of the difference between theory [59] and experiment has been performed in previous work [3,5,8]. Here we provide an updated analysis, which include our new result and the data from Tables VII and VIII .…”
Section: Comparison Between Measurements and Calculations For 12 ≤mentioning
confidence: 92%
“…When older calculations were used as a reference, we used the energies of Ref. [59] to obtain an updated value for this table. A detailed analysis of the difference between theory [59] and experiment has been performed in previous work [3,5,8]. Here we provide an updated analysis, which include our new result and the data from Tables VII and VIII .…”
Section: Comparison Between Measurements and Calculations For 12 ≤mentioning
confidence: 92%
“…[32]. Later, drawing on the x-ray transition measurements in He-like titanium and statistical treatment of the previous experimental data, Chantler et al [33,34] claimed that a divergence between the experimental results and the theory from Ref. [32] growing as Z 3 takes place.…”
Section: Introductionmentioning
confidence: 99%
“…New measurements of the transition energies in middle-Z heliumlike ions have been undertaken [35][36][37][38][39][40], and the obtained results fall outside the Z 3 -trend predicted in Refs. [33,34]. Moreover, new statistical studies [38,40,41], which include the extended sets of experimental data, have shown that there is no evidence for the aforementioned Zdependent deviation.…”
Section: Introductionmentioning
confidence: 99%
“…A new great interest to middle-Z heliumlike ions has been triggered by Chantler and co-authors [33,34]. In Ref.…”
Section: Introductionmentioning
confidence: 99%